2000
DOI: 10.1002/1529-0131(200006)43:6<1371::aid-anr22>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil cytoplasmic antibodies in patients with early rheumatoid arthritis: An early marker of progressive erosive disease

Abstract: In patients with early RA, pANCA are associated with specific serologic markers of RA and predict rapid radiographic joint destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 40 publications
4
26
1
Order By: Relevance
“…ANCA may play some pathogenetic roles in CrGN [18]. P-ANCA was detected in 19-50% of RA patients [12,13] and MPO-ANCA in 0-12% of RA patients without an apparent manifestation of vasculitis [13,19]. In addition, MPO-ANCA could be the consequence of neutrophil destruction within the inflammatory synovial cavity, because it was detected in the synovial fluid of RA patients [20].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…ANCA may play some pathogenetic roles in CrGN [18]. P-ANCA was detected in 19-50% of RA patients [12,13] and MPO-ANCA in 0-12% of RA patients without an apparent manifestation of vasculitis [13,19]. In addition, MPO-ANCA could be the consequence of neutrophil destruction within the inflammatory synovial cavity, because it was detected in the synovial fluid of RA patients [20].…”
Section: Discussionmentioning
confidence: 87%
“…We also reviewed reported cases of biopsy-proven MPO-ANCAassociated CrGN with RA. In this analysis, we excluded cases whose MPO-ANCA-associated CrGN was considered to be related to drug toxicity and cases in whom only perinuclear antineutrophil cytoplasmic antibody (pANCA) was examined because of their high prevalence and variable antigenic specificity among RA patients [12,13].…”
Section: Patients and Selection Criteriamentioning
confidence: 99%
“…ANCA positivity in patients with AS has been reported by several researchers, with 0-28% of AS patients exhibiting ANCA positivity (7)(8)(9)(10). In these reports, the ANCApositive AS patients showed no symptoms of vasculitis or pulmonary manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, the ANCApositive AS patients showed no symptoms of vasculitis or pulmonary manifestations. The ANCA patterns encountered in patients with AS primarily involve P-ANCA, which is considered to be a predictor of chronic and progressive inflammatory joint disease in AS patients (8)(9)(10)(11). Locht et al reported that target antigens (ANCAs) include MPO (2/43 cases) and other minor antigens, such as lactoferrin (3/43 cases) and alpha-antigen (2/43 cases) (8).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that BPI-ANCA acts as one of the persistent stimulatory agents for the production of inflammatory cytokines and does not actually reflect acute changes in disease activity. Although several studies have reported a positive relationship between the titer of pANCA and RA disease activity or joint lesions [9,16], the significant role of ANCAs in RA disease activity remains controversial. Further studies are needed to clarify the pathogenic mechanisms of ANCAs for joint and systemic inflammations in RA.…”
Section: Discussionmentioning
confidence: 99%